Memórias de alfabetizadores matemáticos em processo de formação continuada - SILVA, Fabio Colins da (Universidade Federal do Pará, 2021)
This text is an excerpt of the dissertation entitled "Knowledge Teachers in the/of the Continuing teacher training to teach Mathematics in Literacy Cycle", investigated the teaching knowledge mobilized in the/of the continued training literacy teachers. The research was context the Federal Program National Pact for Literacy in the Age One. The locus of the investigation was the city of Marabá, Pará State, Brazil. The subjects of this study were five literacy teachers. The survey was conducted between March 2014 and January 2015. The construction of the information was given from the records of the activities carried out by literacy teachers during the municipal formation meetings, their practice reports and their experience reports. The methodology used was the analysis Text Analysis Discourse. You can say that through the memories teachers training process can mobilize knowledge required for mathematical literacy practices.